Peer Group Discussion–Based Reproductive Health Education and Adolescents’ Attitudes Toward Early Marriage: A Quasi-Experimental Study - Diadjeng Setya Wardani; Rafi’ Andyah Arum Kedaton; Nabila Sinta Devi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Early marriage is defined as marriage occurring before the age of 19 years. The incidence of early marriage remains high in East Java, Indonesia. Early marriage is associated with limited educational attainment, increased health risks, and emotional instability among adolescents. Adolescence is a critical developmental period during which attitudes and decision-making are strongly influenced by peers. Peer group discussion-based reproductive health education provides an interactive learning approach that may enhance adolescents’ understanding of puberty, reproductive rights, and marriage readiness. This study aimed to analyze changes in adolescents’ attitudes toward early marriage after receiving peer group discussion-based reproductive health education at SMPN 2 Singosari, Malang, East Java. Methods: This study employed a pre-experimental one-group pretest-posttest design without a control group. The research was conducted from November to December 2024. The population consisted of all seventh-grade students (n-256). Using purposive sampling based on inclusion criteria, 72 adolescents were selected as participants. Respondents completed a questionnaire assessing attitudes toward early marriage before and after the intervention. The intervention consisted of structured peer group discussions on reproductive health, facilitated over several scheduled sessions. Data were analyzed using descriptive statistics and the Wilcoxon to assess differences in pretest and posttest attitude scores. Results: The majority of respondents were 13 years old, female and Javanese ethnicity. Some respondents had parents or relatives who married at an early age. Prior to intervention, most adolescents demonstrated a moderate attitude toward early marriage. However, after the intervention, the majority demonstrated a good attitude. The Wilcoxon test yielded a p-value < 0,05 indicating a statistically significant improvement adolescents’ attitudes. Conclusion: Peer group discussion-based reproductive health education significantly improves adolescents’ attitudes toward early marriage. Future research is recommended to include a control group, a longer follow-up and a larger sample size.